ANALISIS KELAYAKAN RESTRUKTURISASI MESIN PABRIK GULA KREMBOONG, KABUPATEN SIDOARJO, JAWA TIMUR - Ariesa, Felicia Nanda; Tinaprilla, Netti; Tinaprilla, Netti (Forum Agribisnis, 2012)
Sugar is one of the staples food that is widely consumed by the public. Sugar demand continued to increase along with increasing growth of population. Sugar factory revitalization made ââin order to support food security system, especially for staples food. Revitalization is aimed for increasing the production capacity of sugar factories, productivity and content of sugarcane and expansion of plantation. Revitalizing sugar factory aims to meet the needs of sugar demand in order to attain self-sufficiency in sugar by 2014. One program of revitalization is the rejuvenation of the old machines which have decreased performance resulting in lower efficiency of sugar mills. Restructuring needs big investment with a long repayment period so that the feasibility analysis is needed to see whether the restructuring Kremboong Sugar Mill machines feasible and can provide better profit. Based on the analysis aspect of the market, technical, socio-economic, and management found that the restructuring of the machine is feasible. This is indicated by the availability of a broad market, a clear corporate management, creation of employment, as well as the accuracy of the use of technology in their production processes. Financial analysis through investments in the eligibility criteria of 14% discount rate produces NPV Rp52.414.490.686,68, IRR of 50%, Net B/C ratio of 3.68, and 8.88-year payback period (8 years 10 months 17 days). From the results of financial analysis can be concluded that the restructuring decent machine to run.